The relationship between anxiety and depression symptoms in insomnia patients: a network analysis - Yu Liu; Zirong Zhu; Jiaran Yan; Yuanyuan Wang (Scientific Reports)
Abstract Anxiety and depressive symptoms are both common in insomnia patients, and they share a critical bidirectional relationship. The available research suggests that transitioning from a disorder-level analysis to a symptom-level analysis may provide a clearer understanding of these relationships. A total of 1571 insomnia patients were enrolled in this study. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), anxiety symptoms were evaluated using the Hamilton Rating Scale for Anxiety (HAM-A), and depressive symptoms were evaluated using the Hamilton Rating Scale for Depression (HAM-D). Subsequently, a network analysis was conducted for the statistical analysis. Among the present sample, the prevalences of depression and anxiety were 87.1% and 88.0%, respectively. We found that the strongest regularized partial correlations existed in the network between “C3: Sleep duration” and “C4: Habitual sleep efficiency” (r = 0.91). Two other strong regularized partial correlations were observed between “B3: Cognitive disturbance” - “B7: Hopelessness” (r = 0.36), “A2: Psychic anxiety” - “B5: Retardation” (r = 0.28). In addition, the item “C3: Sleep duration” had the highest strength centrality in the network, followed by “C1: Subjective sleep quality”, “C4: Habitual sleep efficiency”, “A2: Psychic anxiety”, “B1: Anxiety/Somatization”. The findings highlight the crucial role of the strongest regularized partial correlations and bridge symptoms in relation to depression and anxiety. Targeted interventions for clinical control of anxiety and depressive symptoms in insomnia patients are promising.